Effects of Dietary Supplementation of Garlic (Allium sativum) powder on Growth Performance and Carcass Characteristics of Broilers - Makwana, RB; Bhagat, SR; Parikh, SS; Savaliya, BD; Jadav, CN (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was carried out for six weeks to investigate the effects of adding graded levels (0, 0.1 and 0.5%) of garlic (Allium sativum)powder to the basal experimental diet on the growth performance and carcass characteristics of broiler chicks. One hundred and eighty(n = 180) day old unsexed white commercial broiler chicks (Cobb-400) were randomly distributed into three dietary treatments of 60birds/treatment and each treatment contained 4 replicates (15 birds/replicate). The dietary treatments were controlled basal diet (T1),and a diet supplemented with garlic powder at 0.1% (T2) and 0.5% (T3). Daily feed intake, weekly body weight, and residue leftoverwere recorded to calculate the feed conversion ratio (FCR). At the end of the experiment, six birds from each group were sacrificed todetermine the carcass characteristics. Results revealed that dietary supplementation of 0.1% garlic powder (T2) significantly (p
Keywords: Broilers; Cobb; Dressed yield